Letter from John Wesley Powell to James Curtis Booth, April 30, 1886 - Powell, John Wesley (1886)
John Wesley Powell (1834-1902), first director of the Bureau of Ethnology at the Smithsonian Institution and director of the U.S. Geological Survey, writes to assure James Curtis Booth (1810-1888) that his delay in sending a geological survey report was not the only one encountered. Powell informs Booth that there will be no need for an elaboration of Booth's earlier work of 1837-1840.
Keywords: Powell, John Wesley, 1834-1902; Booth, James Curtis, 1810-1888; Geological surveys; Geological Survey (U.S.); Mint of the United States; United States Mint